Proline, Total Antioxidant Capacity, and OsP5CS Gene Activity in Radical and Plumule of Rice are Efficient Drought Tolerance Indicator Traits - Muhammad Abu Bakar Saddique; Zulfiqar Ali; Muhammad Ali Sher; Babar Farid; Rao Muhammad Ikram; Muhammad Saeed Ahmad (International Journal of Agronomy)
The success of a plant breeding program is linked with the rapid screening of crop germplasm. In the following study, the germination stage of rice seeds has been examined for the rapid screening of drought-tolerant genotypes. The rice genotypes (10 drought tolerant, 5 moderately drought tolerant, and 5 drought susceptible) were sown in Petri dishes under control and osmotic stress of 15% PEG6000. Data were recorded after four days of sowing for the osmotic stress-induced change in imbibition rate, speed of germination, radical and plumule length, radical and plumule total fresh and dry weight, proline contents, total antioxidant capacity, and malondialdehyde level in radical and plumule of seeds. Moreover, the change in expression of OsP5CS gene was also recorded in one of each drought tolerant, moderately drought tolerant, and drought susceptible genotypes. Under osmotic stress, the level of proline, total antioxidant capacity, and the expression of OsP5CS were increased in drought-tolerant genotypes as compared to moderately drought tolerant and drought susceptible genotypes. While, the change in imbibition rate, speed of germination, radical and plumule length, and fresh and dry weight were not symmetrical in drought tolerant, moderately drought tolerant, and drought susceptible genotypes. In short, the symmetrical change in proline, total antioxidant capacity, and expression of OsP5CS gene within radical and plumule of drought tolerant, moderately drought tolerant, and drought susceptible genotypes can help rapid screening of drought-tolerant rice genotypes.